2022
DOI: 10.1097/bpo.0000000000002226
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS Utilization in Pediatric Orthopaedics: A Scoping Review

Abstract: Background: The lack of a common patient-reported outcome metric used among the orthopaedic population is a problem that has been previously identified by the American Academy of Orthopaedic Surgeons. The Patient-Reported Outcomes Measurement Information System (PROMIS) was developed by the National Institute of Health with the goal of creating a precise and efficient measurement tool for patient-reported symptoms, functioning, and health-related quality of life to be used in clinical research. A study summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Pediatric orthopaedics has also observed an upward trend in the administration of PROMIS as an abbreviated yet responsive metric for assessing outcomes. 33 Regarding novel delivery methods, Mellor et al 34 validated the collection of two PROMs in pediatric sports medicine (Pedi-IKDC and Pedi-Fab scale) with automated text messaging and found that mobile PROM delivery provided a valid assessment of these metrics and may increase compliance while reducing the labor cost of collecting paper PROMs. Continued investigation of the use of metrics that allow for increased access will help understand outcomes in novel manners and potentially resolve limitations with PROM compliance.…”
Section: Current Opportunities For Patient-reported Outcome Measures ...mentioning
confidence: 99%
“…Pediatric orthopaedics has also observed an upward trend in the administration of PROMIS as an abbreviated yet responsive metric for assessing outcomes. 33 Regarding novel delivery methods, Mellor et al 34 validated the collection of two PROMs in pediatric sports medicine (Pedi-IKDC and Pedi-Fab scale) with automated text messaging and found that mobile PROM delivery provided a valid assessment of these metrics and may increase compliance while reducing the labor cost of collecting paper PROMs. Continued investigation of the use of metrics that allow for increased access will help understand outcomes in novel manners and potentially resolve limitations with PROM compliance.…”
Section: Current Opportunities For Patient-reported Outcome Measures ...mentioning
confidence: 99%
“…16 PROMIS has been used prior in the pediatric orthopaedic population and has continued to increase in popularity, likely due to its efficiency and reliability. 17 The PROMIS Pediatric Anger and Anxiety item banks (both v1.1) contain 22 and 13 items, respectively, and have demonstrated good performance and appropriate psychometric properties in assessing emotional states across a range of medical diagnoses for children as young as 5 years old (Tables 1, 2). [18][19][20][21] Given the lack of efficient and effective PTSD screening tools in pediatric orthopaedics, the purpose of this study was to evaluate measurement properties of the PROMIS Anger and Anxiety instruments in pediatric patients who have undergone procedures or surgery for orthopaedic trauma and to determine the ability of these instruments to detect those children at risk for developing PTSD when compared with the current standard, the Child PTSD Symptom Scale (CPSS).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Given the lack of efficient and effective PTSD screening tools in pediatric orthopaedics, the purpose of this study was to evaluate measurement properties of the PROMIS Anger and Anxiety instruments in pediatric patients who have undergone procedures or surgery for orthopaedic trauma and to determine the ability of these instruments to detect those children at risk for developing PTSD when compared with the current standard, the Child PTSD Symptom Scale (CPSS). 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation